Sudden death in cattle by Mascagnia sp (Malpighiaceae) in the State of Santa Catarina, Brazil Mortes súbitas em bovinos causadas pela ingestão de Mascagnia sp (Malpighiaceae), no Estado de Santa Catarina - Gava A.* (1998)
In the coastal areas of the State of Santa Catarina occurs a disease in cattle characterized by "sudden death". The disease was reproduced in bovines by oral administration of Mascagnia sp. Single doses of 5 g/kg of the fresch leaves of Mascagnia sp caused non-lethal poisoning; single doses of 7,5 g/kg caused lethal poisoning in one of two bovines and doses of 10 g/kg death in two others. In the experiments clinical manifestations were observed when the animals were exercised. They consisted in weakness, swollen jugular vein, slight muscular tremors and sometimes sudden contractions; tachycardia, already observed before the exercise, became more intense. At the end the animals suddenly laid down or fell on their side. The course of poisoning in those two animals which were followed up till death, was 40 and 75 minutes. The highest doses given (15 and 20 g/kg) caused a protratecd course; the animals got slow and apathic, avoiding any movements. They were found dead, 7h45min and 21 hours after the first clinical signs. These two last experiments show the importance of exercise regarding the onset of symptoms and the occurrence of "sudden death". The main post-mortem findings were intense red discoloration of the mucosa of the small intestine and oedema of the gallbladder wall. The main histological alteration was hydropic vacuolar degeneration of the tubular epithelium of the kidney in three of the five bovines which died.